1879 Tenn. Acts 231, ch. 186, § 1 - (:unkn) unknown (My University, 1879)
Prohibited the public or private carry of any dirk, razor concealed on their person. Also prohibited the open carry of any sword cane, spanish stilletto, belt pistols, pocket pistols, revolver, or any other kind of pistols except Army or Navy pistols. Violators fined fifty dollars and imprisoned in the county of the violation at the court's discretion.
Keywords: CARRY